Updates on the worldwide burden of amoebiasis: A case series and literature review - Jade Nasrallah; Mohammad Akhoundi; Djamel Haouchine; Anthony Marteau; Stéphane Mantelet; Philippe Wind; Robert Benamouzig; Olivier Bouchaud; Robin Dhote; Arezki Izri (Elsevier, 2022)
Background: Amoebiasis is an intestinal and tissue parasitic infection caused by the protozoan Entamoeba histolytica. Despite significant medical importance and worldwide dispersion, little is known about the epidemiology and distinct geographical distribution of various clinical forms of amoebiasis in the world. In this study, we present an amoebiasis case series referred to Avicenne Hospital (Bobigny, France) from 2010 to 2022 followed by an overview of the released literature to explore diverse clinico-pathology of amoebiasis and to update the actual epidemiological situation of this parasitosis worldwide. Methods: The referred patients underwent a combination of clinical and parasitological examinations and imaging. The study was followed by an overview of released literature performed based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guideline. Results: A total of 15 patients with amoebiasis were diagnosed with an average age of 48.5 years old at the occurrence time of infection. Men (78%) were the most affected patients. Most of the cases were reported following a trip to endemic regions, such as Mali, India, Nepal, Algeria, Cameroon or Congo. All of the processed patients exhibited a hepatic amoebiasis. Amoebic abscess was observed in all cases with an average size of 6.3 cm. Of these patients, seven cases (46.7%) benefited from drainage following a risk of rupture or superinfection of the abscess. A compilation of findings extracted from 390 scientific publications via seven major medical databases, allowed us to update the main epidemiological and clinical events that has led to the current worldwide expansion of amoebiasis. We presented a clinical and epidemiological overview of the amoebiasis accompanied with a worldwide illustrative map displaying the current distribution of known amoebiasis foci in each geographical ecozone of Asia, Europe, Africa, Americas, and Australia. Conclusions: Although Metropolitan France is not known as an endemic region of amoebiasis, amoebic liver abscess was the most frequent clinical form observed among our 15 patients processed. Most of infected patients had a history of travel to or lived-in endemic areas before arriving in France.